Concentration, diversity, and consequences: Privileging independent over major record labels. Issue 3 (12th September 2018) - Mall, Andrew
Abstract: The field of popular music studies has long been interested in the relationships between record labels and the music they make available to consumers. At the micro level, research on record labels provides insight into the tensions between art and commerce and those between individuals and institutions. At the macro level, this research illuminates changes in socio-economic trends, music industry structures and structural inequalities. A meta-analysis of this literature reveals an 'indie prejudice': a preference for (and even a bias in favour of) independent labels coupled with a dismissive approach to the study of major labels and musical mainstreams that impacts our ability, as a scholarly field, to speak with authority about the largest segments of the commercial record industries. What larger implications for our scholarship might confronting this prejudice reveal? What master narratives have structured popular music studies' preference of independent over major record labels? In this article, I argue that the art/commerce dichotomy has remained influential, although it can have unintended and dangerous side effects if it becomes a guiding assumption.